La Azolla: importancia y usos para mejorar la fertilidad y calidad del suelo y del agua en la agricultura - Aguiar Arguello, Kevin Omar (2020)
The following document is aimed to learn the benefits of the Azolla fern, its symbiotic relationship with the cyanobacterium Anabaena Azollae and prove if it can improve the quality of water and soil by functioning as a bioremediatory. The document is based on scientific research on Azolla, its production, characteristics, development and uses. Hypotheses will be raised with the information collected, most of the investigations cited are of Ecuadorian origin. This information will serve in the future to make people aware of what Azolla is and what it is for; opening new ideas for future experiments based on this little-known fern and its bioremediation characteristic.